Cyber cafe management system - Mohd Khazro'ie, Jaafar (2010)
Cyber Cafe Management System is software for operating Internet Cafe, Cyber Cafe, Game Center, Gaming Cafe and PC rental Cafe shop It has been designed for use in an Internet coffee shop, cybercafe management, accounting billing, although it can be used for intranet PC controlling. Cyber Cafe Management System is a real-time way to manage the client machines via monitoring and locking in order to process PC rentals which includes the ability to fully control and charge for printing. This thesis consists of 6 chapters. Chapter 1 will discuss about the Introduction to the System. These first chapters briefly explain about the objective of the system ,problem statement and project scopes. Chapter 2 and 3 are about the Literature Review and Methodology of the project. Chapter 2 and 3 will discuss about the methods that will be used, elaborating the sources from the research, and deciding the best tools that will be used to build the system. Chapter 4, Implementation; are about the documentation of the processes during the development of the system ,including any modification that been plan and made. While the last, Chapter 5 Result and Discussion and Chapter 6 Conclusion. Chapter 5 will explain about the result that has collected from the analysis and tests of the system along with the constraints and suggestion to enhance the system performance. Conclusion and overall summary of the system, data, methodology, implementation, and the suggestions are in the matter of the discussion on of the chapter 6.